Starting a Digital Business: Being a Millennial Entrepreneur Innovating - Saryani; Indri Handayani; Rina Agustina (Startupreneur Business Digital (SABDA Journal), 2022)
Indonesia is now entering the era of the Fourth Industrial Revolution or Industrial Revolution 4.0. Therefore, the economic sector's change towards smart business is good, and the progress of existing digital business may contribute to the economic development of Indonesia, especially e-commerce. With the development of information and digital technologies, the business and development competition, which was initially focused on the use of natural resources, will shift to the acquisition of information and digital technologies. This is the importance of innovation in business. The era of Industry Revolution 4.0 opens up opportunities for young millennial entrepreneurs in the business sector to become experts in the latest knowledge and technology development. For this reason, skill improvements and skills updates need to be implemented so that the workforce can compete based on the current needs of industry.